2002
DOI: 10.1007/s003830200001
|View full text |Cite
|
Sign up to set email alerts
|

Megacystis-microcolon-intestinal hypoperistalsis syndrome: evidence of intestinal myopathy

Abstract: We investigated small- and large-bowel specimens of three newborn infants presenting with the clinical and radiological symptoms of megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS). Conventional histological staining revealed marked thinning of the longitudinal muscle layer. Electron-microscopic investigations showed typical "central core" vacuolic degeneration of smooth-muscle-cells combined with proliferation of col lagen fibres. The expression of alpha-smooth-muscle actin was absent or mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…Several hypotheses have been proposed to explain the pathogenesis of MMIHS: genetic [173], neurogenic [172,175], myogenic [167,169,174] and hormonal origin [175,176]. Histological studies of the myenteric and submucosal plexuses of the bowel of MMIHS patients have revealed normal ganglion cells in the majority of the patients, decreased in some, hyperganglionosis and giant ganglia in others [168][169][170][171][172].…”
Section: Megacystis Microcolon Intestinal Hypoperistalsis Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Several hypotheses have been proposed to explain the pathogenesis of MMIHS: genetic [173], neurogenic [172,175], myogenic [167,169,174] and hormonal origin [175,176]. Histological studies of the myenteric and submucosal plexuses of the bowel of MMIHS patients have revealed normal ganglion cells in the majority of the patients, decreased in some, hyperganglionosis and giant ganglia in others [168][169][170][171][172].…”
Section: Megacystis Microcolon Intestinal Hypoperistalsis Syndromementioning
confidence: 99%
“…This syndrome is characterised by abdominal distension caused by a distended non-obstructed urinary bladder, microcolon, and decreased or absent intestinal peristalsis. Usually incomplete intestinal rotation and shortened small bowel are associated [167][168][169][170][171][172][173][174][175][176][177][178].…”
Section: Megacystis Microcolon Intestinal Hypoperistalsis Syndromementioning
confidence: 99%
“…Thinning of the intestinal longitudinal muscle layer and increased connective tissue proliferation between the intestinal smooth muscle layers have also been observed [7]. On electron microscopy, ‘central core' vacuolar degeneration in the center of smooth muscle cells has been described in smooth muscle cells in the bowel and bladder [7,9,10]. Immunohistochemical staining with antibodies against α-smooth muscle actin and caldesmon has shown markedly reduced staining in the longitudinal and circular layers of the small and large bowel and bladder [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On electron microscopy, ‘central core' vacuolar degeneration in the center of smooth muscle cells has been described in smooth muscle cells in the bowel and bladder [7,9,10]. Immunohistochemical staining with antibodies against α-smooth muscle actin and caldesmon has shown markedly reduced staining in the longitudinal and circular layers of the small and large bowel and bladder [8,9,10]. Recently familial [11,12,13] and de novo [13,14] ACTG2 mutations have been implicated in the etiology of familial visceral myopathy (FVM) as well as MMIHS.…”
Section: Introductionmentioning
confidence: 99%
“…Several subsequent reports have confirmed this [165,170,171]. Other investigators have reported absence or marked reduction in the a-smooth muscle actin and other contractile and cytoskeletal proteins in the smooth muscle layers of MMIHS bowel [165,171].…”
Section: Normal Indmentioning
confidence: 63%